Investigation of protein-protein interactions and hotspot region on the NSP7-NSP8 binding site in NSP12 of SARS-CoV-2 - Lima Neto, José Xavier; Bezerra, Katyanna Sales; Barbosa, Emmanuel Duarte; Araujo, Roniel Lima; Galvão, Douglas Soares; Lyra, Marcelo Leite; Oliveira, Jonas Ivan Nobre; Akash, Shopnil; Jardan, Yousef A. Bin; Nafidi, Hiba-Allah; Bourhia, Mohammed; Fulco, Umberto Laino (Frontiers in Molecular Biosciences, 2024)
The RNA-dependent RNA polymerase (RdRp) is a crucial complex for viral transcription and replication, making it a promising target for antiviral drugs like Remdesivir. The core unit of RdRp comprises the nonstructural protein NSP12, with NSP7 and two copies of NSP8 (NSP81 and NSP82) binding to NSP12 to enhance its affinity for viral RNA and polymerase activity. Notably, the interfaces between these subunits are highly conserved, simplifying the design of molecules that can disrupt their interaction.In this study, we conducted a quantum biochemical analysis to characterize the interactions within the NSP12-NSP7, NSP12-NSP81, and NSP12-NSP82 dimers. We aimed to understand the contributions of individual amino acid residues to these protein-protein interactions and identify their hotspot regions.Our findings revealed that the total interaction energy (TIE) was strongest in the NSP12-NSP81 complex compared to the others, with a higher number of interacting pairs. Specifically, 14 pairs of residues in NSP12-NSP81 exhibited the most substantial interaction energies, while eight residue pairs had the strongest interactions in the NSP12-NSP7 complex, and only one pair showed significant interaction in NSP12-NSP82.We also observed the importance of hydrogen bonds and π-alkyl interactions in these complexes.Interestingly, the introduction of an RNA sequence with the antiviral Remdesivir resulted in minimal changes in the interaction energy and geometry of the complexes.In conclusion, our study's insights into the interaction and energetic profile at the protein-protein interface offer valuable guidance for designing small molecules or peptide/peptidomimetic ligands capable of disrupting these interactions.